1993
DOI: 10.1021/np50097a016
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Screening Strategy for the Dereplication and Prioritization of HIV-Inhibitory Aqueous Natural Products Extracts

Abstract: A relatively high percentage (ca. 15%) of aqueous extracts from terrestrial plants, cyanobacteria, and marine invertebrates and algae has exhibited activity in the National Cancer Institute's primary AIDS-antiviral screen. By removal of anionic polysaccharides in a first stage of dereplication, we have eliminated from further consideration a considerable number of these extracts. However, a still substantial proportion of the active extracts remained, from which we wished to select and prioritize a small perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 10 publications
0
59
0
3
Order By: Relevance
“…In some cases it has become a common procedure to remove tannins from plant extracts before biological activity tests are conducted (Cardellina et al, 1993). However, in the present work and also in other studies (Kashiwada et al, 1992), it has been shown that some hydrolysable tannins display selective cytotoxicity.…”
Section: Resultsmentioning
confidence: 51%
“…In some cases it has become a common procedure to remove tannins from plant extracts before biological activity tests are conducted (Cardellina et al, 1993). However, in the present work and also in other studies (Kashiwada et al, 1992), it has been shown that some hydrolysable tannins display selective cytotoxicity.…”
Section: Resultsmentioning
confidence: 51%
“…The authors concluded that the extracts contained RT inhibitors that &&are at least novel among the blue-green algae'' (Lau et al, 1993). Cardellina et al (1993) reported that about 15% of aqueous extracts from terrestrial plants, cyanobacteria, and marine invertebrates and algae exhibited HIV-antiviral activity in the National Cancer Institute's primary AIDS-antiviral screen. A considerable number of extracts were eliminated after removing anionic polysaccharides.…”
Section: 34mentioning
confidence: 99%
“…Alternatively, the simplest explanation is that the effects of EGCG on many of its reported molecular targets are merely high-concentration effects or experimental artifacts that reflect the propensity of catechins and other polyphenolic substances to chelate metals and bind proteins in a nonselective manner (reviewed in Haslam, 1996). This is the main reason that the high-throughput pharmaceutical screening community has considered polyphenols and other tannins to be "nuisance" compounds that must either be removed from test samples or dereplicated prior to extensive evaluation in protein-based bioassay systems (i.e., enzyme or receptor) (Cardellina et al, 1993). If this is the case, only a relatively small number of the numerous molecular mechanistic studies reported for EGCG and other green tea products actually reflect physiologically relevant processes.…”
Section: Introductionmentioning
confidence: 99%